Peran Orang Tua dan Teman Sebaya dalam Meningkatkan Learning Motivation Anak Berkebutuhan Khusus Usia SD/MI. - Rahayu, Ade; Saskia, Arna (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Inclusive education is key to ensuring equal access to learning for Children with Special Needs (CSN), particularly those who are tunawicara (speech-impaired) and face verbal communication barriers. This study examines the roles of parents and peers in enhancing learning motivation among tunawicara students in inclusive age elementary schools, emphasizing the critical influence of socio-emotional factors on learning success. Employing an analytical library research method based on Miles and Huberman’s framework, data were drawn from journals, legal documents, and credible literature. Findings reveal that parents play a strategic role through emotional support, home-based speech training, and school collaboration, while peers function as peer tutors and social mediators who boost self-confidence and verbal interaction. Together, they synergistically foster an inclusive and motivating learning environment. The study affirms that inclusive education requires more than infrastructure—it demands active participation from families and peer groups